Optimizing exposure‐based CBT for anxiety disorders via enhanced extinction: Design and methods of a multicentre randomized clinical trial. Issue 2 (21st March 2017) - Heinig, Ingmar; Pittig, Andre; Richter, Jan; Hummel, Katrin; Alt, Isabel; Dickhöver, Kristina; Gamer, Jennifer; Hollandt, Maike; Koelkebeck, Katja; Maenz, Anne; Tennie, Sophia; Totzeck, Christina; et al.
Abstract: Exposure‐based psychological interventions currently represent the empirically best established first line form of cognitive‐behavioural therapy for all types of anxiety disorders. Although shown to be highly effective in both randomized clinical and other studies, there are important deficits: (1) the core mechanisms of action are still under debate, (2) it is not known whether such treatments work equally well in all forms of anxiety disorders, including comorbid diagnoses like depression, (3) it is not known whether an intensified treatment with more frequent sessions in a shorter period of time provides better outcome than distributed sessions over longer time intervals. This paper reports the methods and design of a large‐scale multicentre randomized clinical trial (RCT) involving up to 700 patients designed to answer these questions. Based on substantial advances in basic research we regard extinction as the putative core candidate model to explain the mechanism of action of exposure‐based treatments. The RCT is flanked by four add‐on projects that apply experimental neurophysiological and psychophysiological, (epi)genetic and ecological momentary assessment methods to examine extinction and its potential moderators. Beyond the focus on extinction we also involve stakeholders and routine psychotherapists in preparation for more effective dissemination into clinical practice.